Politik Primordial dan Politik Identitas dalam Perkembangan Demokrasi dan Politik Lokal Di Indonesia - Satryo Pringgo Sejati; Ahmad Burhan Hakim (Universitas Sunan Drajat Lamongan, Indonesia, 2023)
Indonesia is one of the Muslim countries in the world that is able to gradually implement democracy in its political system. In the 25 years after the reform, Indonesia has tried various schemes to be able to carry out democratization so that it can be accepted by the Indonesian people themselves and even aims to get a positive international image. In the dynamics that occur, the development of political democracy in Indonesia gives rise to a social and political dynamics known as primordial politics and identity politics. These two approaches become true when we look at the conditions and dynamics of politics and democracy that occur in Indonesia. Moreover, the position of the regions has a significant role in contributing to the development of democracy and politics at the center. The region is an interesting area to discuss considering that the region is part of the political administration which has a strong influence on the center. This happened during the Indonesian reformation that occurred in 1998. Where the centralized concept became decentralized with the emergence of regional autonomy. In other words, the region has full power and authority to determine its political and economic direction. Of course, under other conditions it would be better. But on the other hand there are sociological consequences that must be accepted after the reform. The development of democracy in Indonesia actually produces primordial politics and identity politics, which are difficult to avoid. So it could be that Indonesia itself is aware that these two approaches are indeed taking place and cannot be avoided. Therefore, it is necessary for us to understand that primordial politics and identity politics today are a social reality and fact that occur in the dynamics of politics and democracy in Indonesia.